2000
DOI: 10.7326/0003-4819-132-7-200004040-00009
|View full text |Cite|
|
Sign up to set email alerts
|

Single-Therapy Androgen Suppression in Men with Advanced Prostate Cancer

Abstract: Survival after therapy with an LHRH agonist was equivalent to that after orchiectomy. No evidence shows a difference in effectiveness among the LHRH agonists. Survival rates may be somewhat lower if a nonsteroidal antiandrogen is used as monotherapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
218
0
48

Year Published

2002
2002
2016
2016

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 426 publications
(271 citation statements)
references
References 46 publications
5
218
0
48
Order By: Relevance
“…On the basis of the NMA, together with a paper 12 and poster 13 which do not include one of the comparators (triptorelin), the company assumed that the efficacy and safety profiles of the LHRH agonist comparators were equivalent. The ERG considered the assumption that the LHRH agonists: goserelin; leuprorelin and triptorelin are clinically equivalent to be unproven and therefore inappropriate.…”
Section: Critique Of Clinical Evidence and Interpretationmentioning
confidence: 99%
“…On the basis of the NMA, together with a paper 12 and poster 13 which do not include one of the comparators (triptorelin), the company assumed that the efficacy and safety profiles of the LHRH agonist comparators were equivalent. The ERG considered the assumption that the LHRH agonists: goserelin; leuprorelin and triptorelin are clinically equivalent to be unproven and therefore inappropriate.…”
Section: Critique Of Clinical Evidence and Interpretationmentioning
confidence: 99%
“…The effects of pure anti-androgen treatment have been compared to those of medical or surgical castration in randomized trials in men with metastatic prostate cancer. Although these drugs seem to be better tolerated, they are inferior therapies in terms of overall and progression-free survival 33,34 .…”
Section: Boxmentioning
confidence: 99%
“…Cyproterone, a steroid compound, was the first anti-androgen, but it was soon discovered that the drug binds AR both in the prostate and in the hypothalamus and pituitary, thereby inhibiting the negative feedback mechanism and ultimately leading to LH release and increased testosterone levels (55). To circumvent this problem and to reduce discomforting, sexual side effects caused by surgical or medical castration, drug companies developed non-steroidal anti-androgens, including flutamide and bicalutamide, but randomized trials have demonstrated that these drugs are not as effective as castration or LHRH inhibitors (60). Clinical trials have also been performed to assess the effectiveness of combining treatments, for example using a LHRH agonist with a non-steroidal anti-androgen, but meta-analyses have shown that such an approach confers only modest to no benefit versus therapy with a single drug (61,62).…”
Section: Androgen Deprivation Therapy For Advanced and Metastatic Dismentioning
confidence: 99%